1998
DOI: 10.1111/j.1540-8159.1998.tb01156.x
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Septal Pacing to Synchronize Atrial Depolarization in Patients with Delayed Interatrial Conduction

Abstract: The current method of pacing the right atrium from the appendage or free wall is often the source of delayed intraatrial conduction and discoordinate left and right atrial mechanical function. Simultaneous activation of both atria with pacing techniques involving multisite and multilead systems is associated with suppression of supraventricular tachyarrhythmias and improved hemodynamics. In the present study we tested the hypothesis that pacing from a single site of the atrial septum can synchronize atrial dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 11 publications
3
35
0
1
Order By: Relevance
“…They showed that the right atrial appendage pacing resulted in the longest duration of activation within both atria as compared to the Bachmann's bundle and the in teratrial septum [4,[12][13][14][15]. The stimulation of the interatrial septum is deemed by many research ers to be the best pacing placement with regards to the activation time of both atria, which seems to be in line with the theoretical model [16,17]. In some studies this kind of atrial pacing was also combined with paroxysmal atrial fibrillation pre vention [18,19].…”
Section: Discussionsupporting
confidence: 53%
“…They showed that the right atrial appendage pacing resulted in the longest duration of activation within both atria as compared to the Bachmann's bundle and the in teratrial septum [4,[12][13][14][15]. The stimulation of the interatrial septum is deemed by many research ers to be the best pacing placement with regards to the activation time of both atria, which seems to be in line with the theoretical model [16,17]. In some studies this kind of atrial pacing was also combined with paroxysmal atrial fibrillation pre vention [18,19].…”
Section: Discussionsupporting
confidence: 53%
“…It was shown that the stimulation of the right atrial appendage results in the longest activation of both atria in comparison to the Bachmann's bundle (13) and interatrial septum pacing site (7,(14)(15)(16). The stimulation of septum is considered in many papers to be the best pacing place with regard to the both atria activation time (17)(18)(19), which seems to be concordant with a theoretical model. In some p a p e r s t h i s k i n d o f a t r i a l stimulation site was also combined with the prevention of paroxysmal atrial fibrillation (20,21).…”
Section: Wwwintechopencommentioning
confidence: 58%
“…The histological structure of the Bachmann's bundle fascicles resembles more the Purkinje fascicle than the working muscle cells resulting in a faster interatrial conduction and thus shortening the P wave duration (50). The stimulation of the Bachmann's bundle shortens both atria electrical activation, shortens the P wave, improves the symmetry of the left atrial activation, shortens also the sinus node recovery time (18). The long-term electrophysiological properties (sensing, pacing threshold, resistance) of the Bachmann's bundle region in terms of permanent pacing are comparable with that of right atrium appendage.…”
Section: The Antiarrhythmic Properties Of Atrial Pacingmentioning
confidence: 99%
“…16 Rationale for septal pacing and reduction of P-wave duration Bradycardia, disturbances of the autonomic nervous system, atrial dilatation, atrial stretch, and the presence of triggers (including atrial premature beats) are factors, which predispose to paroxysmal AF. 2,[17][18][19] These factors cause loss of homogeneity of refractoriness and conduction. Pacing can abolish several of these factors.…”
Section: Electrical Activation Of the Atriamentioning
confidence: 99%
“…[1][2][3][4][5][6] There is growing evidence to suggest that pacing at the atrial level in the region of Bachmann's bundle, the interatrial septum (IAS) or even multiple atrial sites may have advantages in patients with atrial fibrillation. [6][7][8][9][10] However, these specific site pacing techniques require extremely accurate lead positioning compared with those used for conventional bradycardia indications.…”
Section: General Considerations: Specific Site Pacing Techniquesmentioning
confidence: 99%